From ‘Apartheid’ to the ‘Rainbow Nation’ and beyond : the representation of childhood and youth in South African coming-of-age narratives - Patterson, Rebecca Rachelle (Stellenbosch : Stellenbosch University, 2017)
Thesis (MA)--Stellenbosch University, 2017.